Lateral translocation of surface soil by various no-till narrow point openers - Solhjou, A. A.; Fielke, J.; Desbiolles, J. (Agrociencia Uruguay, 2012)
Australian no-till farming often uses narrow point openers to open the soil and place seed and fertilizer in a furrow. They are generally used in conjunction with spraying of herbicides for weed control and press-wheels to pack soil over seeds. These openers when operating at speeds beyond 8 km/h can create excessive soil throw which creates problems of increased weed burden and reduced seeding quality, which can also enhance crop establishment risks due to herbicide damage and soil moisture loss. This work uses the results of surface PVC tracer displacement to estimate the likely movement of soil applied pre-emergent herbicide, typically incorporated during the no-till seeding operation, and evaluate the effects of furrow opener geometry. Three variations to opener design were evaluated; four rake angles of 35, 53, 72 and 90°, three leading edge conditions of blunt, chamfered one side and chamfered both sides, and a range of five bent leg openers. The effect of the various narrow opener geometries on soil movement and furrow profile were evaluated in a soil bin with a sandy loam soil and at a forward speed of 8.2 km/h and a depth of 120 mm. Results showed that the openers with various rake angles all threw surface soil at least 300 mm from the center and this would land in an adjacent furrow when used at typical row spacings. A low rake angle of 35° had the least lateral surface soil movement and the 53° rake angle gave the widest band of soil, along the tool path, that was cleared of surface tracers. Adding a chamfer to the leading edge reduced lateral soil movement when compared to a blunt opener. The bent leg opener achieved much lower soil movement while loosening a furrow, and when combined with a single sided chamfer was able to virtually eliminate throwing of soil out of the furrow and hence would have no effect on adjacent furrows. The concept of bent leg furrow openers has the potential to change the dynamics of soil disturbance when no-till seeding with tine openers.